Structure and activity of the RNA-targeting Type III-B CRISPR-Cas complex of Thermus thermophilus - Staals, Raymond H.J. (2013)
The CRISPR-Cas system is a prokaryotic host defense system against genetic elements. The Type III-B CRISPR-Cas system of the bacterium Thermus thermophilus, the TtCmr complex, is composed of six different protein subunits (Cmr1-6) and one crRNA with a stoichiometry of Cmr1(1)2(1)3(1)4(4)5(3)6(1):crRNA(1). The TtCmr complex co-purifies with crRNA species of 40 and 46 nt, originating from a distinct subset of CRISPR loci and spacers. The TtCmr complex cleaves the target RNA at multiple sites with 6 nt intervals via a 5’ ruler mechanism. Electron microscopy revealed that the structure of TtCmr resembles a ‘sea worm’ and is composed of a Cmr2-3 heterodimer ‘tail’, a helical backbone of Cmr4 subunits capped by Cmr5 subunits, and a curled ‘head’ containing Cmr1 and Cmr6. Despite having a backbone of only four Cmr4 subunits and being both longer and narrower, the overall architecture of TtCmr resembles that of Type I Cascade complexes.